MENEJMENT NAZARIYASI ASOSIDA UMUMIY O‘RTA TA’LIM TASHKILOTLARIDA BOSHQARUV TEXNOLOGIYALARINI JORIY QILISHNING TARIXI - Mamayusupova, M.Q. (SCIENCE and SOCIETY, 2025)
This topic analyzes the complexity of management in the development of the educational system, changes in management practices at different historical stages, and their connection with modern management methods and innovative approaches.
Keywords: general secondary education; management; management evolution; educational institu tions; educational system; education and upbringing; management methods; pedagogical management; school of management